Nível de perda de inserção periodontal em pacientes do sexo feminino da clínica de periodontia da Faculdade de Odontologia de Araçatuba - Unesp - Botton, Vivian Moraes [UNESP] (2009)
This study has the objective to evaluate the record of 428 females patients attended on the Odontology University from Araçatuba - UNESP in relation to the level of clinical loss of attachment, analyzing if there happen a pattern in clinical periodontal attachment loss provoked by periodontit. The measures were obtained in millimeters in the six sites per tooth from the union cementoenamel until the periodontal pocket depth or gingival sulcus. The patients clinical records were analyzed individually, delineating a minimum, medium and maximum value of clinical loss of attachment for each patient. According to the methodology applied in this study was possible to prove that the periodontal disease does not provoke a regular pattern in a periodontal loss of attachment